Experience and Nature - Dewey, John (Dover Publications Inc., 1925)
Here is an enlarged, revised edition of the Paul Carus lectures which Dewey delivered in 1925. It covers Dewey's basic formulation of the problems of knowledge, with both a full discussion of theories and resolutions propounded by other systems, and a detailing of Dewey's own concepts upon the relationship of the external world, the mind, and knowledge.